2016
DOI: 10.5455/medarh.2016.70.473-476
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Lipoleiomyoma of the Uterus: an Unusual Case

Abstract: Introduction:Uterine lipoleiomyomas are a rare type of uterine myomas, which have been seldom diagnosed and are less known and still unusual. Histologically they are composed of smooth muscle cells with multiple fat cells and fibrous tissue. Their pathogenesis is still a stigmata and their preoperative diagnosis is still questionable.Case report history:A 39-year old woman presented at the University clinic for obstetrics and gynecology with complaints of a mild low abdominal and pelvic pain, increased frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The proportion of the fatty component within the lesion is highly variable and may be shown as an almost entirely fatty neoplasm simulating lipoma. Several pathogenetic mechanisms underlying the presence of fat cells within leiomyoma have been discussed previously [3][4][5]16]. Although the direct transformation (metaplasia or Our study demonstrated that adipocytic transdifferentiation, as shown by intracellular lipid accumulation and the enhanced expression of adipogenic markers (i.e., adiponectin, perilipin-1), can be elicited in cultured uterine leiomyoma cells by XAV939 treatment together with serum starvation and hypoxia.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The proportion of the fatty component within the lesion is highly variable and may be shown as an almost entirely fatty neoplasm simulating lipoma. Several pathogenetic mechanisms underlying the presence of fat cells within leiomyoma have been discussed previously [3][4][5]16]. Although the direct transformation (metaplasia or Our study demonstrated that adipocytic transdifferentiation, as shown by intracellular lipid accumulation and the enhanced expression of adipogenic markers (i.e., adiponectin, perilipin-1), can be elicited in cultured uterine leiomyoma cells by XAV939 treatment together with serum starvation and hypoxia.…”
Section: Discussionmentioning
confidence: 54%
“…The phenomenon is most commonly encountered in neoplastic conditions of smooth muscle cells such as leiomyomas and angiomyomas [1][2][3]. However, the detailed mechanisms underlying adipocytic transdifferentiation remain largely unknown; however, the adipocytic differentiation of pluripotent mesenchymal cells in such lesions and the direct transformation of neoplastic smooth muscle cells are possible explanations [3][4][5].…”
mentioning
confidence: 99%